Efficacy of the Treatment of Elderly Trauma Patients Requiring Intensive Care - Oshima, Kiyohiro; Murata, Masato; Aoki, Makoto; Nakajima, Jun; Sawada, Yusuke; Isshiki, Yuta; Ichikawa, Yumi; Fukushima, Kazunori; Hagiwara, Shuichi; Hinohara, Hiroshi (Emergency Medicine International, 2018)
Purpose. To evaluate the effectiveness of intensive care for the elderly trauma patients aged 80 years and older. Methods. Trauma patients admitted to the intensive care unit (ICU) through the emergency room (ER) at our hospital between January 2013 and December 2016 were analyzed. Patients were divided into two groups: patients aged 80 and older (group E) and <80 years old (group Y). Clinical courses and the total treatment costs were compared between the two groups. Data are shown as median (interquartile range). Results. A hundred and seven trauma patients were included in the study. There were 26 patients in group E and 81 patients in group Y. There was no significant difference in Injury Severity Score (ISS) (group E, 19 (13, 32); group Y, 17 (14, 25); p=0.708); however, the probability of survival (Ps) was significantly lower in group E (group E, 0.895 (0.757, 0.950); group Y, 0.955 (0.878, 0.986); p=0.004). The duration of ICU stay (days) was significantly longer in group E (10 (5, 23)) than in group Y (4 (3, 9); p=0.001), and the total hospital stay (days) was longer in group E (33 (13, 57)) than in group Y (22 (12, 42); p=0.179). The hospital mortality was higher in group E (11.5%) than in group Y (6.2%) without a significant difference (p=0.365). The total treatment costs were significantly higher in group E ($23,558 (12,456, 42,790) with $1 = ¥110.57) than in group Y ($16,538 (7,412, 25,422); p=0.023). Conclusions. Elderly trauma patients require longer-term treatment including ICU stay and greater cost with higher hospital mortality compared with young trauma patients.